Coupled Thermo-Electromagnetic microstructural modeling of inductive aggregate blends. (4th October 2021) - Karimi, Mohammad M.; Darabi, Masoud K.; Rushing, John F.; Cox, Benjamin C.
Graphical abstract: Highlights: A coupled thermo-electromagnetic constitutive relationship was proposed. The optimum size of inductive particles was determined in microstructural modeling. The induction heating was conducted on diverse aggregate-inductive particle blends. The effect of the microstructure of blends on induction heating was investigated. The temperature variation versus time at different points of blends was studied. Abstract: A numerical framework is proposed to investigate the effect of steel particles on thermo-electromagnetic response of asphalt concrete aggregate blends. To investigate the effect of microstructural properties on induction heating, aggregates were blended with steel particle with various microstructural characteristics (e.g., size, shape, and geometry). Ampere's, Maxwell-Faraday's, Guess's, Ohm's and Joule's laws were coupled to the Fourier's and Newton's laws to properly capture heat generation and transfer through conduction and convection mechanisms. Experimental studies were conducted by applying electromagnetic fields to aggregate blends containing inductive particles with different microstructural properties. Microstructural representation of the aggregate blends were reconstructed computationally based on the gradation and properties of aggregates and steel particles. Coupled thermo-electromagnetic simulations were conducted to investigate how microstructural properties of inductive particles affect the induction heating of the aggregate blend. Simulation results as compared to experimental measurements confirm the efficiency and accuracy of the coupled thermo-electromagnetic microstructural simulations. The results are used to determine the optimum design that yields the most efficient inductive aggregate blends.